2018
DOI: 10.3390/cells7090119
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Immunoregulatory function of Nlrp12 in T Cell-Mediated Immune Response: Lessons from Experimental Autoimmune Encephalomyelitis

Abstract: Although the etiology of multiple sclerosis (MS) remains enigmatic, the role of T cells is unquestionably central in this pathology. Immune cells respond to pathogens and danger signals via pattern-recognition receptors (PRR). Several reports implicate Nlrp12, an intracellular PRR, in the development of a mouse MS-like disease, called Experimental Autoimmune Encephalomyelitis (EAE). In this study, we used induced and spontaneous models of EAE, as well as in vitro T cell assays, to test the hypothesis that Nlrp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
(85 reference statements)
2
21
2
Order By: Relevance
“…It has been previously reported that 2D2 + mice develop spontaneous EAE with low incidence (0 to 20%) when housed under SPF conditions (16,(23)(24)(25)(26). We observed EAE incidence to be higher in our 2D2 + colony, with ∼25% of mice developing classic EAE signs including tail and hind-limb paralysis (Table 1).…”
Section: Resultssupporting
confidence: 61%
“…It has been previously reported that 2D2 + mice develop spontaneous EAE with low incidence (0 to 20%) when housed under SPF conditions (16,(23)(24)(25)(26). We observed EAE incidence to be higher in our 2D2 + colony, with ∼25% of mice developing classic EAE signs including tail and hind-limb paralysis (Table 1).…”
Section: Resultssupporting
confidence: 61%
“…To measure the total protein expression of glutamate transporters, intracellular staining was performed (protocol modified from Gharagozloo et al 2018 and Schwarz et al 2013) [58,59]. WT and Nlrx1 -/- astrocytes were washed with phosphate-buffered saline (PBS), fixed, permeabilized, and blocked with 5% dFBS in washing buffer.…”
Section: Methodsmentioning
confidence: 99%
“…CNS tissue was digested with 2.5 mg/mL collagenase D (Roche Diagnostics, Indianapolis, IN, 11088866001) and 1 mg/mL DNase I (Sigma-Aldrich, St. Louis, MO, 11284932001) and filtered through a 70-μm nylon sieve as described previously [12]. Mononuclear cells were isolated by percoll (Sigma-Aldrich, St. Louis, MO) centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…T-cell proliferation was quantified using 3 H-thymidine incorporation assay and Ki67 intranuclear staining following fixation and permeabilization using Foxp3/Transcription Factor staining kit (eBioscience, San Diego, CA, 00-5523-00). Intracellular staining of cytokines was performed as previously described [12]. Sample acquisition was performed with Beckman Coulter CytoFlex and data were analyzed using CytExpert 2 software (Beckman Coulter).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation